Assessing the Factors Effecting Women with Polycystic Ovarian Syndrome - Laila Shahzad, Saba Ilyas Ahmed Malik, Huma Tahseen, Shabana Khokhar, Saima Qurban, Samar Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Polycystic ovary syndrome (PCOS) is a leading disease in females now a days, and also considered as a main cause of infertility in females. The symptoms of the disease PCOS is appeared in the reproductive age and after puberty in young age. The current study is conducted through online google forms to make community outreach possible. It is considered as a asocial taboo therefore many women were reluctant to be part of the study and to sow their identity. Results showed that the perception of women about the pcos condition provide a lot of stress and trauma. 30.6% women strongly agreed that PCOS is the major cause of weight gain and therefore recommended to change the life style and have active day routine. It was assessed that this condition affect hormonal imbalance in females and irregularity in periods. More in-depth studies are needed to understand the relationship of this disease with diet and lifestyle factors.